Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan(Studi Pada Konsumen Assalam Hypermarket) - Ika Ratnaningtyas, Yuni, Ir. Irmawati, S.E., M.Si (2017)
This research aimed to analyze the effect of product uality, service quality and customer satisfaction to customer yalty. independent variables consist of product quality, service quality and customer satisfaction and the dependent variable is customer loyalty.This research was conducted in Assalam Hypermarket using sampling methods (probability sampling) with a sample of 176 respondents who shopped at Assalam Hypermarket. The analysis in this research was to test the validity, reliability test, t test, F test, lassicassumption test, multiple linear regression analysis and coefficient of determination (R2).The results of this study indicate that the product quality has significant positive effect on customer loyalty, service quality has significant positive effect on customer loyalty and customer loyalty has nificant positive effect on2customer loyalty. For simultaneous F test results of product quality, service quality and customer satisfaction significantly influence customer loyalty. For the coefficient of determination (R2) is explained as much as 35,6% customer loyalty can be explained by the variable product quality, service quality and customer satisfaction while the remaining 64,4% is explained by other variables that are not described in this research.